(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2004)
The detailed sedimentary and micropalaeontological analysis of a complex association of continental to marginal-marine deposits from the Oxfordian of Portugal (Cabaços Formation) has allowed the recognition of high-frequency, subtle changes in the environmental conditions. The main factors controlling the palaeobiological responses to such minor-scale fluctuations were also identified. Two factors have shown to be especially significant: subaerial exposure duration and frequency (estimated by assigning type of features to the exposure index) and salinity trends, as suggested by the sedimentary and fossil records. In the west of the basin, salinity fluctuations were much stronger and more frequent (fresh- brackish-restricted marine-hypersaline), and subaerial exposure more marked for longer periods, than in the east of the basin. The microfossil assemblages, as a whole, but in particular the ostracod faunas, show differences in abundance, diversity, dominant species, degree of intrageneric and intraspecific variations, both along the successions and between west and east. The western populations seem to have been much less stable, which suggests that high-frequency changes in salinity (more than its absolute values) and degree of exposure were the most important controls on the palaeobiota. PDF